A psychometric assessment of a network social capital scale among sexual minority men and gender minority individuals - Meagan Zarwell; Jennifer L. Walsh; Katherine G. Quinn; Andréa Kaniuka; Alexandra Patton; William T. Robinson; Robert J. Cramer (BMC, 2021)
Abstract Background Social capital, the potential for individuals to access resources through group memberships, is linked to a constellation of health outcomes. We modified a previously evaluated Constructed Family Social Capital Scale for gay, bisexual and other men who have sex with men who belong to constructed families to create a new measure of social capital within sexual minority men and gender minority individuals' social networks. Methods Participants were recruited from a Pride festival in Milwaukee, Wisconsin in 2018 to complete a cross-sectional survey. This analysis is restricted to 383 participants who identified as sexual minority men or gender minority individuals and completed nine items measuring social capital within their social networks. We conducted exploratory and confirmatory factor analyses to assess factor structure. Internal consistency was measured using Cronbach's alpha. Results Reliability was high, indicating the scale's utility to assess Network Social Capital among sexual minority men and gender minority individuals. A single-factor solution with high factor loadings was found for the nine-item scale. Conclusions This study extended the psychometric properties of a preliminary social capital instrument modified from a prior study in a different population and context. The modified measure has implications for use among sexual minority men and gender minority individuals to measure social capital within social networks. Previous studies suggest that interventions to enhance social capital among sexual minority men and gender minority individuals may be beneficial for HIV prevention interventions. This tool may be relevant for the evaluation of social capital interventions within networks of sexual minority men and gender minority individuals.